Exploring psychological distress in the lives of those affected by homelessness - Greenwood, Hannah (2021)
This portfolio thesis is comprised of three parts and considers the experience of homelessness and psychological distress, from the perspectives of those with lived experience. Part one: Systematic Literature Review Part one contains a systematic literature review which explores the influences on homeless service users’ experience and perception of mental health services. A systematic search of six data bases retrieved ten suitable papers, the findings of which are presented using narrative synthesis. Three overarching influencing factors and ten sub-factors emerged. Conclusions and clinical implications for service development are discussed. Part two : Empirical paper Part two is a qualitative empirical study which explored how previously homeless White British males make sense of distressing unusual experiences and beliefs, by hearing their stories. A narrative oriented inquiry framework applied four analytic perspectives to analyse the stories’ content, form and identity positions. Conclusions and implications for practice are considered. Part three: Appendices Part three consists of the appendices supporting both previous parts. A reflective and epistemological statement is included.
HydraID: hull:18392 Hydra Discover Access Group: public ETD Collection: ETDClinicalBiosciences
Keywords: Clinical psychology